Service Demands and Challenges of Healthcare System in Nepal - Sigdel, Rishav Dev (Socio-Economic Development Panorama, 2009)
Health care system is a broad activity in all over the world. Increasing health care demands both in developed and underdeveloped nations are serious phenomenon. Health care system of the USA is getting very expensive for non-working people as well as for little income generating people. A health care demand in Nepal is also unprecedented increment in terms of delivering an effective and efficient health care service for the poorest of the poor. Health care practices and delivery need to be revised time to time to increase its quality of services. Nepal is facing serious epidemics each year in the public health sector. The calamities of major diseases include water and air borne pollution. Mountain water in monsoon is over flood each year and the Terai plain became harsh land for inhabitants. Majority people victimized with diarrhea and its infections due to contamination over regular using water of households. At the situation of flood, people are desperate to access clean water supply for drinking and using their daily needs for crucial activities in their temporary tents and huts. One major reason Nepalese people die each year in an alarming rate in the remote villages. Nowadays, respiratory infection and its related problems is another killer. It is also growing in the villages as well in big cities in Nepal. However, the disturbing news on health concerns falls apart; people need to be aware of these major destroyers. Initiative plans and programs of public health care introduced for a long time ago; the reality of healthcare practices in Nepal is not effective to the poorest of the poor. Neck and neck posture of donors is very crucial to eradicate a major focused diseases, or in reality, to reduce an overall human disasters in Nepal. UN along with NGOs roll is tremendous, but they are not in fast tracks to deal with the public demands of health care services that is growing increasingly. They need to be ready to tackle new challenges to carry on slogan of improving public health in forthcoming days. Key words: Healthcare system; biosensor; awareness activities and programs; diseases; government; NGOs; Public; Red Cross; PM10; plans/programs; health care practice; health care facilities; medical treatment Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June